Characteristics of Environmentally Friendly Food Container Composite Made From Sorghum Bagasse and Citric Acid - ismadi, ismadi; Kusumah, Sukma Surya; Subyakto, Subyakto; Subiyanto, Bambang; Suryanegara, Lisman; Marlina, Resti (Jurnal Bahan Alam Terbarukan, 2020)
The common food container product was made from plastic such as polypropylene, polystyrene, etc which has slowed to degrade hence affected to the environmental pollution and health disorder. Therefore, environmentally friendly food container composite is developed from sustainable resources such as sorghum bagasse and citric acid. The effects of sorghum species, sorghum particles and citric acid content on the composite properties were investigated. Local species of sorghum was used as raw material such as Super 2 in the manufacturing of food packaging. The size and moisture content of the particles were passthrough on 40 mesh and 10%, respectively. The content of the particle was variated such as 10, 15, and 20% wt. Furthermore, citric acid was used as a binder with difference content such as 10, 20, and 30% wt. Those raw materials were mixed with tapioca starch, polyvinyl alcohol (PVA), and glutaraldehyde. The mixing material was hot pressed at 180 ℃ for 15 minutes. The composite dimension was 12 cm x 10 cm x 3 mm. The physical and mechanical properties of the composite were carried out. Considering the properties of the composite, sorghum bagasse and citric acid are suitable as raw material of food container composite.